2019
DOI: 10.1371/journal.pone.0217125
|View full text |Cite
|
Sign up to set email alerts
|

Measuring brand association strength with EEG: A single-trial N400 ERP study

Abstract: Companies need to ensure that customers perceive their brands as intended, with strong and unique associations, when facing a competitive market. Traditionally, brand associations are measured using conventional techniques such as surveys and questionnaires albeit both conscious and unconscious factors can influence the collected data and the outcome of a campaign. Neuromarketing can shed light on how the customer’s brain processes marketing stimuli. We report here on an EEG study aimed at gauging mental assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…Brown et al ( 2012 ) use a simple study with soft drinks to answer this question: even when the taste of a soft drink is identical, participants tend to prefer the known brand, reporting higher perceived pleasantness, showing low price elasticity, and displaying high amplitude value in the alpha spectrum over the frontal lobe area (associated with emotions). In a study on brand association, Camarrone and Van Hulle ( 2019 ) present a series of combinations of familiar brands and common words. The amplitude of the event-related potential components N400 indicates the incongruence between two concepts and is used to reveal associations between brands, product categories, and consumers' emotions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Brown et al ( 2012 ) use a simple study with soft drinks to answer this question: even when the taste of a soft drink is identical, participants tend to prefer the known brand, reporting higher perceived pleasantness, showing low price elasticity, and displaying high amplitude value in the alpha spectrum over the frontal lobe area (associated with emotions). In a study on brand association, Camarrone and Van Hulle ( 2019 ) present a series of combinations of familiar brands and common words. The amplitude of the event-related potential components N400 indicates the incongruence between two concepts and is used to reveal associations between brands, product categories, and consumers' emotions.…”
Section: Resultsmentioning
confidence: 99%
“…This notion becomes particularly relevant when dealing with decision-making processes in which non-conscious mechanisms are involved. As an example, using EEG and ERP, Camarrone and Van Hulle ( 2019 ) were able to reveal associations between brands, product categories, and emotions that would have otherwise gone unnoticed with conventional surveys. Further promising is the identification of EEG-derived indices as predictors of commercial success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the literature shows a lack of research, enabling to highlight how brand associations may be modified by communication activities, in particular to websites communication strategies. Some research experiments already presented significant results about methods to measure brand image based on the constellation of associations (Till et al, 2011;Schnittka et al, 2012;Camarrone and Van Hulle, 2019). Some other research projects showed how brand associations can be efficiently applied to advertising assessments (Janakiraman et al, 2009;Anderson and Simester, 2013;Caldato et al, 2020).…”
Section: Related Research Workmentioning
confidence: 99%
“…This essential response highlights the capabilities in language assessment. It • Semantic categorization/global understanding transmits the capacity of the patient in the semantic process [13]. The N400 component is controlled by an immediate context such as a word a couple of words, or an image.…”
Section: Introductionmentioning
confidence: 99%